Interspecific Recombination Between Zucchini Tigre Mosaic Virus and Papaya Ringspot Virus Infecting Cucurbits in China - Peng, Bin; Liu, Liming; Wu, Huijie; Kang, Baoshan; Fei, Zhangjun; Gu, Qinsheng (Frontiers in Microbiology, 2021)
Recombination drives evolution of single-stranded RNA viruses and contributes to virus adaptation to new hosts and environmental conditions. Intraspecific recombinants are common in potyvirids, the largest family of single-stranded RNA viruses, whereas interspecific recombinants are rare. Here, we report an interspecific recombination event between Papaya ringspot potyvirus (PRSV) and Zucchini tigre mosaic potyvirus (ZTMV), two potyviruses infecting cucurbit crops and sharing similar biological characteristics and close phylogenetic relationship. The PRSV-ZTMV recombinants were detected through small RNA sequencing of viruses infecting cucurbit samples from Guangxi and Henan provinces of China. The complete nucleotide (nt) sequences of the interspecific recombinant viruses were determined using overlapping RT-PCR. Multiple sequence alignment, recombination detection analysis and phylogenetic analysis confirmed the interspecific recombination event, and revealed an additional intraspecific recombination event among ZTMV populations in China. The symptoms and host ranges of two interspecific recombinant isolates, KF8 and CX1, were determined through experimental characterization using cDNA infectious clones. Surveys in 2017 and 2018 indicated that the incidences of the interspecific recombinant virus were 16% and 19.4%, respectively, in cucurbits in Kaifeng of Henan province. The identified interspecific recombinant virus between PRSV and ZTMV and the novel recombination pattern with the recombination site in HC-pro in potyvirid provide insights into the prevalence and evolution of ZTMV and PRSV in cucurbits.